Genetic and molecular genetic studies of sporophytic self- incompatibility in senecio squalidus - Lou, Y (2018)
Angiosperms are the most successful group of land plants in terms of their diversity, abundance and distribution. In order to ensure obligate outcrossing, hermaphrodite flowers have evolved elaborate systems of pollen-pistil recognition, including self-incompatibility (SI). Research on SI systems in many families such as Brassicaceae, Papaveraceae, and Solanaceae has shown that a range of divergent molecular mechanisms is involved in different families even when they share the same genetic basis. Therefore, to better understand the evolution of these processes in angiosperms and the molecular diversity of SI, one UK species, Senecio squalidus (Oxford Ragwort) is taken as an Asteraceae model species to investigate pollen-pistil recognition and SI. This project characterized further the genetics of sporophytic SI (SSI) in S. squalidus, in particular the dominance interactions between S haplotypes. Among its low number of S haplotypes, novel dominance interactions were observed in pollen (male gametophyte). Then to identify the S locus, genomic maps of model plants in the Asteraceae family (sunflower, lettuce, chicory and Tolpis coronopifolia) that are reported to contain molecular markers or quantitative trait loci (QTL) associated with SI or self-fertility, were analyczed to identify any shared region. Pairwise comparisons between these genome sequences were conducted and aslo their synteny pattern with the draft genome sequence for S. squalidus were searched. Some synteny was revealed between lettuce and Tolpis. At the same time, a few linkage groups of S. squalidus are highlighted to contain the S locus potentially. Finally, the expression pattern and polymorphism between S genotypes were investigated for a candidate S gene belonging to the Leucine-Rich Repeat Receptor-Like Kinase (LRR-RLK) family. All the available LRR-RLK homolog sequences of S. squalidus were analyzed. Through molecular experiments, they shown to lack the tissue-specific expression pattern and polymorphism characteristics predicted for an S gene. So they are considered not to be the S determinant of S. squalidus. Together, these three lines of researches provide new insights into the genetic and molecular genetic basis of SSI in S. squalidus, and establish a better foundation for further research on SI in S. squalidus and Asteraceae generally.